Cross-polarization effects in sheared 2D grating couplers in a photonic BiCMOS technology. (12th May 2020) - Georgieva, Galina; Voigt, Karsten; Mai, Christian; Seiler, Pascal M.; Petermann, Klaus; Zimmermann, Lars
Abstract: We investigate numerically and experimentally sheared 2D grating couplers in a photonic BiCMOS technology with a focus on their splitting behavior. Two realization forms of a waveguide-to-grating shear angle are considered. The cross-polarization used as a figure-of-merit is shown to be strongly dependent on the grating perturbation strength and is a crucial limitation not only for the grating splitting performance, but also for its coupling efficiency.